2013
DOI: 10.1094/phyto-11-12-0280-r
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Potential Vectors and Reservoirs of Cucurbit aphid-borne yellows virus in Southeastern Spain

Abstract: The genetic variability of a Cucurbit aphid-borne yellows virus (CABYV) (genus Polerovirus, family Luteoviridae) population was evaluated by determining the nucleotide sequences of two genomic regions of CABYV isolates collected in open-field melon and squash crops during three consecutive years in Murcia (southeastern Spain). A phylogenetic analysis showed the existence of two major clades. The sequences did not cluster according to host, year, or locality of collection, and nucleotide similarities among isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 53 publications
3
39
1
7
Order By: Relevance
“…Our results also showed the infection of S. irio and C. colocynthis as the reservoir hosts for CABYV in planting area of this country, as well. Although Kassem et al (11) have suggested the CABYV infection for Senecio vulgaris and Lamium amplexicaule, no infection was found among the collected samples from these species in this investigation. Our data suggest that weeds could be a critical factor in the maintenance and dissemination of the CABYV infections in cucurbit crops.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Our results also showed the infection of S. irio and C. colocynthis as the reservoir hosts for CABYV in planting area of this country, as well. Although Kassem et al (11) have suggested the CABYV infection for Senecio vulgaris and Lamium amplexicaule, no infection was found among the collected samples from these species in this investigation. Our data suggest that weeds could be a critical factor in the maintenance and dissemination of the CABYV infections in cucurbit crops.…”
Section: Discussioncontrasting
confidence: 82%
“…CABYV is one of the most important yellowing viral diseases of the cucurbit crops (11,20) as it can cause yield losses up to 40-50% in the cucumber and melon, if the infection occurs at an early stage (7). In Iran, also CABYV is one of the most prevalent viruses in the major cucurbit crops and has been detected in the main cucurbit producing provinces; both in the greenhouses as well as open fi eld plantation areas (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This changing environment may favour the emergence of new viruses and vectors (Navas‐Castillo et al , ). For instance, during the last 15 years, production of cucurbits in Western Mediterranean countries has been seriously compromised by a series of successive epidemics caused by Cucurbit yellow stunting disorder virus (CYSDV; Célix et al , ), Cucumber vein yellowing virus (CVYV; Cuadrado et al , ) and Cucurbit aphid‐borne yellows virus (Kassem et al , ).…”
Section: Introductionmentioning
confidence: 99%